2016
DOI: 10.1016/j.avsg.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Uptake and Adherence Rates to Supervised Exercise Programs in Patients with Intermittent Claudication

Abstract: Reporting of SEP trials was poor with regard to the numbers of subjects screened and reasons for exclusions. Only approximately 1 in 3 screened IC patients was suitable for and willing to undertake SEP. Levels of adherence to SEPs and definitions of satisfactory adherence were also lacking in most the current literature. Current clinical guidelines based on this evidence base may not be applicable to most IC patients and changes to SEPs may be needed to encourage and/or retain participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
162
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(176 citation statements)
references
References 77 publications
11
162
3
Order By: Relevance
“…Even when supervised exercise is provided to PAD patients without costs, such as in a research program many PAD patients decline participation. 18 …”
Section: Supervised Treadmill Exercise For Peripheral Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Even when supervised exercise is provided to PAD patients without costs, such as in a research program many PAD patients decline participation. 18 …”
Section: Supervised Treadmill Exercise For Peripheral Artery Diseasementioning
confidence: 99%
“…Of 1,541 potential participants without critical limb ischemia who had sufficient ischemic symptoms to be eligible for inclusion in supervised exercise studies, 769 (50%) reported lack of interest or simply refused participation in supervised exercise and an additional 295 (19%) reported that attending supervised exercise was too inconvenient. 18 Overall, 69% of eligible PAD participants refused participation in supervised exercise. In summary, this systematic review demonstrated that even when supervised exercise was available without cost to the participant with PAD, approximately 2/3 of people with PAD declined participation.…”
Section: Supervised Treadmill Exercise For Peripheral Artery Diseasementioning
confidence: 99%
“…Supervised exercise programs are recommended to improve functional status and reduce leg symptoms and should be discussed as a treatment option for patients with intermittent claudication before revascularization (Gerhard‐Herman et al ). However, a systematic review from 2016 reported that only 1 in 3 patients with intermittent claudication were suitable for and willing to participate in supervised exercise programs (Harwood et al ). For patients with severe PAD, endovascular or open surgery may be options to achieve revascularization, but the ability to perform endovascular or open surgery depends on the localization and extent of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…National governing bodies recommend a supervised exercise programme as the first line treatment, along with best medical therapy [25]. If supervised exercise is not feasible, acceptable or accessible for patients [17] then more invasive therapies, such as angioplasty or bypass surgery may be utilised. Quality of life (QoL) is an important outcome measure with the World Health Organization (WHO) defining it as “physical, social and mental well-being and not just an absence of infirmity” [31].…”
Section: Introductionmentioning
confidence: 99%